The Asset Forfeiture Bill in the Perspective of Criminal Law Policy and the Rule of Law: Between Urgency and Legislative Obstacles - Nahor, T. Banjar (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The legislative process of the Draft Bill on Asset Forfeiture (RUU PA) reflects the complex interplay of law and politics within Indonesia’s legal system. Despite its widely acknowledged urgency as an instrument to recover state losses from corruption and money laundering, the bill has yet to be enacted up to the 2025–2026 National Legislation Program. This study seeks to address two central questions: (1) why the Asset Forfeiture Bill has not been passed until now, and (2) how legal, political, and institutional factors influence its formation, and how its formulation can balance the effectiveness of asset recovery with the protection of human rights. Employing a normative juridical method complemented with socio-legal analysis, the study finds that delays in enactment are driven by normative debates on non-conviction based asset forfeiture (NCB), political bargaining within the House of Representatives, and institutional limitations in managing forfeited assets. The study concludes that the ideal formulation of the bill must integrate the principles of the rule of law, establish strong judicial oversight, and strengthen institutional capacity to ensure that NCB mechanisms operate effectively without undermining constitutional rights. Thus, the Asset Forfeiture Bill should not only function as a tool for state asset recovery but also embody Indonesia’s commitment to justice and the rule of law.